ROLE OF CORPORATE DISCLOSURE ON REPUTATION AND LOYALTY DEVELOPMENT FOR BANKING ORGANIZATION - Hadher Sabah Shair; Salam Hussein Jasim; Mohammed Hameed Nayyef (Scholar Express Journals, 2022)
Disclosure of corporate affairs and financial information helps the company to attract the investors for the investment in company. The purpose of this study is to investigate the role of corporate disclosure on the reputation and loyalty development of banking organization. For the investigation panel data regarding financial performance disclosure on the stock prices of selected banks in India have been examined with the help of E-views software. Secondary data have been collected from the official websites of the banks. Various statistical tools have been applied namely, Panel regression, correlation and unit root test. Finding of the study indicated that corporate disclosure plays important role in building reputation and loyalty development for the banking organization.
Keywords: Banks; Corporate disclosure; Reputation; Loyalty Development